Methodological Bases of Development of Branch Financial Strategy - Murad Kamilovich Alimuradov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Companies in Russian economy different industries develop under condition of high level economic environment dynamics, changes of technologies and raising of internal and international competition. Under such conditions to achieve some level of sustainable results from investing projects without using the strategic approach in the process of long-term financial goals and objectives determination becomes too difficult. In the article we describe the essence of using the strategic approach to financial decision making process in the different industries. We suggest the principle scheme of company financial strategy development. In the article the strategic approach implementation to the different branches companies financial development features are developed. The branches financial strategy stages and their sequences are determined. The mechanism of financial strategic decisions making in company capital structure determination, production potential creation by formation of working capital and fixed assets and investing activity is described. We pointed to the correlation between the financial economic results analysis methods and strategic investing decision making process. In the article the interrelation between the financial forecasting and strategizing processes is pointed. We note that this two processes are not substitutes - the forecasts are not the part of financial strategy and used just as a basis to formulate strategic statements. The results of the article may be used by financial specialists in the different industries to prepare strategic financial papers. Financial strategies developed in accordance with the suggested mechanism have the high potential of efficient implementation.